Mothers Awareness of their Children’s Dental Status: A Study among a Group of Mothers of Children Diagnosed with Early Childhood Caries - Sumer M. Alaki; Sara M. Bagher (Journal of King Abdulaziz University: Medical Sciences, 2023)
Mothers’ dental awareness has an important impact on their children’s oral health and oral health-related behavior. The aim was to evaluate mothers awareness of their childrens dental health status and assessing the effect of different socio-demographic variables on their awareness. A total of 124 healthy children diagnosed to have caries were included together with their mothers. The mothers answered a self administrated questionnaire regarding different socio-demographic variables, their children dental status and dental history. Most of the mothers included were aware of their childrens dental status; 70 (56.5%) were aware that their children have caries. Significantly, more Saudi mothers were aware that their children have caries compared to non Saudi mothers (p = 0.04). Working mothers were also significantly more aware (p = 0.007). Most of the mothers 90 (65.3%) reported that they did not take their child to a dentist before and in those who did, pain was the main cause of their children first dental visit. Significantly, Saudi working mothers and higher (p = 0.037) percentage of mothers who took their child to a dentist were aware of their child dental status.